Išmaniosios sutartys: teisinis reglamentavimas ir jo problematika - Bartkutė, Emilija; Gumbytė, Gabrielė (Vilnius University Open Series, 2020)
This research paper deals with the Institute of Smart Contracts, reveals legal regulation and its problems. In the first part of the work, using the attributes: immutability, specific form and operation without third party mediation, and the basic functions of storing, validating and executing, the concept of smart contracts is revealed. Also, in order to fully disclose the exclusivity of these contracts, fundamental differences from automated transactions are discussed. In the second part – three contract institutes are distinguished, in the context of which the compatibility of smart contracts with the Civil Code of the Republic of Lithuania is assessed. First of all, it discusses the formation and its characteristics, in addition it is evaluated whether the formation of the smart contract violates the norms of the Civil Code of the Republic of Lithuania. Further, the exclusive execution of these contracts and their compliance with Chapter XVI of the Civil Code of the Republic of Lithuania is disclosed. Finally, the paper examines possible breaches of smart contracts, ways to resolve them, as well as customization and compatibility.
Keywords: none